Eko : scaling up a fintech start-up in volatile market and regulatory environments - Vohra, Neharika, 1966- (SAGE business cases., 2022)
The brothers Abhishek and Abhinav Sinha co-founded Eko India Financial Services Pvt. Ltd in 2007. Eko started as a business correspondent (BC) for banks, providing account-opening and cash-in/cash-out (CICO) services for the financially underserved segment in India. In January 2008, they onboarded the Centurion Bank of Punjab (CBoP) as their first banking partner. Eko persisted and brought in the State Bank of India (SBI) as a partner in early 2009; it also raised some funding and ran a pilot project successfully for the SBI. In late 2010, it partnered with ICICI Bank and attempted to increase its transaction volumes. Meanwhile, the start-up ran out of money and was deep incrisis. It bounced back and succeeded in building a business on account of its relationships with distributors and retailers.The company was on a growth path when, in 2015, it developed a domestic money transfer (DMT) solution through its prepaid payment instrument (PPI) licence. This helped Eko achieve INR 20 billion in transaction volumes. Eko extended its technology to its network of small retail outlets (merchants) to help them remit cash digitally over its mobile platform. In 2016, Eko monetised its technological assets and opened its platform for entrepreneurs in the DMT business. At the case closure, Eko was chiefly facing a dilemma of growth, while the co-founders pondered to take the business to another level.